Application of e-tailing strategies for apparel on-line sales - Cudel, Irwin Joseph V.
The purpose of the study is to determine the applicability of identified e-tailing strategies for apparel online sales. Specifically, it aims to: (1) analyze the applicability of identified e-tailing strategies to local apparel e-tailing, and (2) to determine the level of receptiveness of local consumers to identified e-tailing strategies. The foreign apparel e-tailers chosen for this study are successful e-tailer members of Shop.org, a Boston based organization of which there are 358 member e-tailers. Their experience in e-commerce/ e-tailing will benefit this research in evaluation the strategies they use for apparel e-tailing. This study was based on eight recommended strategies by successful e-tailers which are: (1) developing relationships of trust and security with customers; (2) "imprinting" new customers by providing great customer service that translates to customer loyalty; (3) exploiting the connectivity of the Web; (4) providing end-to-end customer service throughout the purchasing cycle; (5) providing customers with more information to help them make better purchasing decisions; (6) leveraging offline relationships to gain online customers; (7) develop interactive merchandising and; (8) creating powerful brand promise around the total retail experience. A survey research design was chosen using the survey-questionnaire and interview schedule. Purposive sampling was used since the respondents had to be established foreign companies that have been implementing the strategies mentioned in. The choice of consumers though was randomly selected an questionnaires were given to them for the purpose of measuring their satisfaction level. Interviews were conducted by e-mail to foreign e-tailing professionals to obtained e-tailing strategies applied to apparel e-tailing. There is an attempt to describe and determine the the applicability of foreign e-tailing strategies to local apparel e-tiling. These strategies help in meeting the apparel e-tailers goal of getting a consumer base, selling and marketing their products on the Internet. The survey also reveals that these strategies help in meeting the requirements of consumers for online shopping. These strategies augmented the products or service they promoted, and results of these strategies supplemented their e-tailing goals and objectives. Furthermore, the consumers had a high level of receptiveness and acceptance for some of the strategies employed by foreign apparel e-tailers. Strategies for promoting brand image, and providing information for better purchasing decisions, and customer service rated higher than other strategies presented. The high level of satisfaction maybe just by the experience of the respondents towards the apparel e-tailers to evaluate their present e-tailing strategies in order to accumulate consumer acceptance. Evaluation means not copying or imitating the strategies used by successful foreign apparel e-tailers rather than developing their own strategies based on the winning formulas for effective apparel e-tailing. In addition the local e-tailers especially those in apparel may consider the researchers findings that the consumers actually visiting and doing transactions with foreign e-tailers may be related whether the products they chose are locally unavailable or better products are offered. Researchers may do an in-depth descriptive study on the benefits local apparel e-tailing companies can gain from implementing and developing their online strategies. Other researchers may do a study on the different aspects of e-commerce applicable for apparel which they are manufacturing, direct advertising and point-of-purchase communications, etc. other researchers can do a comparative study on e-tailing strategies of foreign apparel companies.